Bachelard et Jankélévich, philosophes de L’eau. Quelques Fragments De Philosophie De L’imaginaire - Clero, Jean-Pierre (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2024)
No one would think of bringing together the philosophy of Bachelard and the philosophy of Jankélévitch; so far are, at first sight, their ordinary fields of work. Yet, both have attempted a philosophy of the imaginary that runs against the grain of an ordinary way of practicing it. Indeed, most of time, the visual image is used as a reference by the authors who, at the XXth century, have tried it without they ever explain their choice. The two men, who knew each other for having been professors at the same time at the Sorbonne, who certainly read each other – at least, Jankélévitch quotes Bachelard –, take the opposite of speaking of the image as if it was necessarily visual, transcendant, and on the contrary they manifest a property of immanence of the imaginary, and therefore choose music as the principal scheme of the imaginary. This choice goes without saying for Jankélévitch who was a pianist ; it is less evident and follows winding paths in the work of Bachelard who, avoiding to take the objects of the vision as privileged referents of a reflection on the imagination, is in the presence of the elements – water, earth, fire, air – that are neither objects nor things. These elements are told and dreamed through poetry and music, which is not necessarily instrumental – pianistic – as it is for Jankelevitch, but is adapted to them for reasons that never ceased to bring the two authors together. We will try to take account of this astonishing connection and we will attempt to keep it through the notion of fiction into which neither of them sought to dig, but into which they seem to bequeath a work.